Mengatasi Kekhawatiran: Analisis Matius 6:34 Dalam Konteks Kontemporer - Lestari Br. Silaban; Reni Herayani Manik; Flesia Nanda Uli Boangmanalu; Anessa Mei Pasaribu (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2024)
Worry is a person's feeling or mental condition that arises as a result of fear or anxiety about a certain thing or situation. The challenges of human life in the contemporary context, such as worries about financial pressure, work that never comes and so on, will have a negative impact on their body, spirit and soul. However, Jesus was present and gave teachings and advice on how to overcome anxiety. This is a teaching that really helps the lives of believers in today's contemporary context. The Gospel of Matthew 6:34 provides essential insight and understanding of how God loves His people. The method used is a qualitative method which aims to answer human concerns. The results of the study show that what believers need to do in the contemporary context in overcoming worry is to realize that worry is not useful. Jesus wants His people to prioritize Him in all things so that Jesus, who is full of love, will love His people by providing for all the needs of His people and humans too. You are required to be able to make peace with the situation by thinking positively by making the situation comfortable for yourself.